2021
DOI: 10.1002/hup.2820
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose ketamine infusion in treatment‐resistant double depression: Revisiting the adjunctive ketamine study of Taiwanese patients with treatment‐resistant depression

Abstract: Background: Whether a single low-dose ketamine infusion may have rapid antidepressant and antisuicidal effects in patients with treatment-resistant double depression remains unclear.Methods: This study enrolled 35 patients with treatment-resistant double depression, 12 of whom received 0.5 mg/kg ketamine, 11 received 0.2 mg/kg ketamine, and 12 received normal saline as a placebo. The patients were assessed using the 17item Hamilton Rating Scale for Depression (HDRS) prior to the initiation of infusions, at 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Researchers found that the higher dosing (0.5 mg/kg) led to a significant reduction in depression and suicidal symptoms but not in anxiety distress symptoms. The lower dose (0.2 mg/kg) did not show a rapid reduction in depression symptoms and suicidal ideation 40 . A systematic review of 6 randomized, placebo‐controlled double‐blind clinical trials completed between 1990 and 2013 with participants diagnosed with unipolar and bipolar MDD diagnoses showed that ketamine can rapidly improve depressive symptoms both one day and 7 days after infusion 41 .…”
Section: Modern Psychedelic‐assisted Therapymentioning
confidence: 95%
See 1 more Smart Citation
“…Researchers found that the higher dosing (0.5 mg/kg) led to a significant reduction in depression and suicidal symptoms but not in anxiety distress symptoms. The lower dose (0.2 mg/kg) did not show a rapid reduction in depression symptoms and suicidal ideation 40 . A systematic review of 6 randomized, placebo‐controlled double‐blind clinical trials completed between 1990 and 2013 with participants diagnosed with unipolar and bipolar MDD diagnoses showed that ketamine can rapidly improve depressive symptoms both one day and 7 days after infusion 41 .…”
Section: Modern Psychedelic‐assisted Therapymentioning
confidence: 95%
“…The lower dose (0.2 mg/kg) did not show a rapid reduction in depression symptoms and suicidal ideation. 40 A systematic review of 6 randomized, placebo-controlled double-blind clinical trials completed between 1990 and 2013 with participants diagnosed with unipolar and bipolar MDD diagnoses showed that ketamine can rapidly improve depressive symptoms both one day and 7 days after infusion. 41 Another systematic review of 28 primary studies demonstrated that a single infusion of ketamine reduced clinical depression symptoms within 24 hours and that the benefits were sustained for between 6.8 and 30 days for the 4 single-infusion studies that measured relapse times.…”
Section: Clinical Applications and Researchmentioning
confidence: 99%
“…In the only positive trial of esketamine, people allocated to placebo improved by a huge 17.0 points on the Montgomery-Åsberg Depression Rating Scale over 4 weeks. 3 Having said this, we accept that people may occasionally gain insights through the use of psychoactive substances, though this is not necessarily restricted to psychedelics, and there are safer routes to personal development such as exercise, art, exposure to nature and psychotherapy.…”
Section: Author Reply 31 January 2022mentioning
confidence: 99%
“…Subjective ‘happiness’ during ketamine infusions, for example, appears to predict antidepressant response over time. 3 Crucially, this acute effect predicts responses at follow-up assessment points beyond the mere ‘hours’ mentioned by Horowitz and Moncrieff, and rather extends to 2 weeks post-administration. These and other data suggest that positively experienced drug intoxication in carefully screened, well-controlled and psychologically informed treatment contexts can occur safely 4 and mediate subsequent benefits that persist well beyond the day of administration.…”
mentioning
confidence: 93%
See 1 more Smart Citation